Building and locational characteristics’ quality of purpose-built offices in Malaysia and their relationship with rentals / Edie Ezwan Mohd Safian - Mohd Safian, Edie Ezwan (Institute of Graduate Studies, UiTM, 2016)
Purpose-built office (PBO) market in Malaysia has shown positive developments and increasing level of competitiveness. Many characteristics of PBO were unveiled by virtue of recent studies, market demand, and technology growth and new guidelines/ standards in order to fulfil the property market participants’ need. As a result, the characteristics of Malaysia’s PBO have become more complex. The increasing complexity of characteristics would entail greater needs on their influence on the rental levels of the PBO space. Nevertheless, there is a lack of research in the country that had actually studied in detail the influence of both the building and locational characteristics on rental levels alone in Malaysia. Therefore, the purpose of this thesis is to establish the building and locational characteristics’ quality of PBO and their relationship with rentals in the Malaysia’s office property market. Integral to achieve this objective, various characteristics that cover all fields are grouped under eight categories. Delphi Method has been selected as a reliable qualitative method according to the local context in developing building and locational characteristics of ranking through the eyes of local expert panels that can deliver guidance to researcher in recognising the quality of each characteristics of PBO in the local environment. In line with the gap of knowledge in relation to the need to adopt a more consumer oriented approach and the utilisation of high level spatial technology to refine the measurement of variables, modification and improvement based on the current method that is Building Quality Index (BQI) has been applied into this research…